Making Room for the Needy: The Credit-Reallocation Effects of the ECB’s Corporate QE - Arce, Óscar; Mayordomo, Sergio; Gimeno, Ricardo (Review of Finance, 2021)
We analyze how the ECB’s purchases of corporate bonds under its Corporate Sector Purchase Programme (CSPP) affected the financing of Spanish firms. We first document that the announcement of the CSPP in March 2016 raised firms’ propensity to issue bonds. The flipside was a drop in the demand for bank loans by bond issuers. Around 75% of the drop in loans previously made to debt issuers was redirected to other, smaller nonbond issuing firms. This reallocation process was led by banks with weaker liquidity positions experiencing credit outflows, which extended credit to the same firms they were rationing prior to the CSPP. This positive credit supply shock raised the real investment of nonissuing firms. The concomitant ECB’s Targeted Longer-Term Refinancing Operations (TLTRO-II) is estimated to have contributed to amplifying the credit-reallocation effect triggered by the CSPP.